2018
DOI: 10.1038/s41467-018-04632-8
|View full text |Cite
|
Sign up to set email alerts
|

Network biology discovers pathogen contact points in host protein-protein interactomes

Abstract: In all organisms, major biological processes are controlled by complex protein–protein interactions networks (interactomes), yet their structural complexity presents major analytical challenges. Here, we integrate a compendium of over 4300 phenotypes with Arabidopsis interactome (AI-1MAIN). We show that nodes with high connectivity and betweenness are enriched and depleted in conditional and essential phenotypes, respectively. Such nodes are located in the innermost layers of AI-1MAIN and are preferential targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 71 publications
(139 reference statements)
4
83
0
1
Order By: Relevance
“…We have reinforced previously described intra- and interspecific convergence of effector targeting with effectors from two new species [11, 12], and showed at the same time that most effector targets are pathogen specific (Fig 2 and S2). Our analyses also supported the previously described tendency of effectors to interact with plant proteins better connected and central in the network [43, 45], and showed that this tendency is even stronger among effector hubs, multi-pathogen targets and bacterial core T3E targets (Table 2 and Fig S5).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We have reinforced previously described intra- and interspecific convergence of effector targeting with effectors from two new species [11, 12], and showed at the same time that most effector targets are pathogen specific (Fig 2 and S2). Our analyses also supported the previously described tendency of effectors to interact with plant proteins better connected and central in the network [43, 45], and showed that this tendency is even stronger among effector hubs, multi-pathogen targets and bacterial core T3E targets (Table 2 and Fig S5).…”
Section: Discussionsupporting
confidence: 90%
“…In this work, by compiling our experimental interactomic data on Xcc and Rps and the literature-curated interactions from a wide variety of other pathogen effectors, we extended the notion that effectors tend to privilege interactions with host proteins with higher Ath degree and betweenness centrality [43, 45]. Furthermore, we showed that this tendency is stronger among effector hubs compared to single targets and among multi-pathogen effector targets compared to pathogen-specific targets.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…This includes the above described degree, betweenness, information centrality, PageRank index and load centrality as well as additional features such as eigenvector centrality (a measure of the influence of a node in a network), closeness centrality (reciprocal of the sum of the length of the shortest paths between the node and network), harmonic centrality (reverses the sum and reciprocal operations of closeness centrality and weighted k -shell decomposition) (an edge weighting method based on adding the degree of two nodes in network partition). While weighted k -shell decomposition analysis was recently performed to increase the predictability of host targets of bacterial pathogens 35 , we showed that the top 5% of nodes reside in the inner layers of CSI (Fig. 3a, Supplementary Data 2).…”
Section: Resultsmentioning
confidence: 93%
“…This could also show that target proteins are in general more connected to other proteins of the host species within the intra-species protein-protein network. This can be achieved by using approaches such as the centrality measurements [6] or K-shell decomposition [7]. In addition, several studies have used these datasets and applied them to other closely related species or species that are targeted by specific microbe that lakes PPI.…”
Section: Introductionmentioning
confidence: 99%